Predictive markers of atrial fibrillation in patients after acute ST-elevated myocardial infarction (the results of observational program “FAKEL”) - I. A. Zolotovskaya; I. I. Davydkin; D. V. Duplyakov; V. A. Kokorin (Кардиоваскулярная терапия и профилактика)
Aim. To assess probability of atrial fibrillation (AF) in patients after ST-elevated myocardial infarction (STEMI) with undergone primary percutaneous coronary intervention (PCI).Material and methods. Prospective study in the period from December 2015 to November 2017 was carried out with consecutive inclusion of 107 patients at outpatient follow-up stage after STEMI who have undergone primary PCI. The mean age of patients was 69,5+7,8 years (40 (37,4%) women). Follow-up period was 18 months and included three visits (V): V1 — when included in the study, V2 — after 12 months, and V3 — after 18 months. The endpoints of the study were cases of first diagnosed AF, cardioembolic stroke and death. At all visits predictive markers (Willebrand factor, Cystatin C, N-terminal prohormone of brain natriuretic peptide (NT-proBNP), galectin-3) in the blood plasma were determined.Results. After 18 months of follow-up period in 19 (17,8%) patients were diagnosed AF, 5 of them (4,7%) had cardioembolic stroke, and 3 patients died. Median time of AF development from the onset of STEMI was 308 days. Cox multivariate analysis showed that the risk factors for first diagnosed AF were NT-proBNP — relative risk (RR): 1,05; 95% confidence interval (CI): 0,99-1,10 (p=0,038), cystatin C — RR: 1,44; 95% CI: 0,98-2,12 (p=0,043), galectin-3 — RR: 1,20; 95% CI: 1,03-1,40 (p=0,022).Conclusion. There was a highly significant relationship between NT-proBNP of ≥400,0 pg/mL, cystatin С of ≥1,45 ng/mL and galectin-3 of ≥25 mg/mL in patients after STEMI who underwent primary PCI. These markers might serve as predictors of first diagnosed AF. Identification of these biomarkers may have potential therapeutic benefit in improving the prognosis of patients after STEMI who have undergone primary PCI and reduce mortality from cardioembolic stroke.